2018
DOI: 10.1177/1947603518783503
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage Repair of the Pediatric and Adolescent Knee with Regard to Minimal Clinically Important Difference: A Systematic Review

Abstract: Objective To perform a systematic review of clinical outcomes following microfracture (MFX), autologous chondrocyte implantation (ACI), osteochondral allograft transplantation (OCA), and osteochondral autograft transplantation system (OATS) to treat articular cartilage lesions in pediatric and adolescent patients. We sought to compare postoperative improvements for each cartilage repair method to minimal clinically important difference (MCID) thresholds. Design MEDLINE, Web of Science, Scopus, and Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…23 In the majority of clinical studies, clinical scores decrease at mid- and long-term follow-up. 23,36 It has also been shown that the outcome of MF is much better in small defects (<2-4 cm) 2,8,24,37 and has a worse outcome in localized cartilage defects >4.5 cm. 2,8…”
Section: Discussionmentioning
confidence: 98%
“…23 In the majority of clinical studies, clinical scores decrease at mid- and long-term follow-up. 23,36 It has also been shown that the outcome of MF is much better in small defects (<2-4 cm) 2,8,24,37 and has a worse outcome in localized cartilage defects >4.5 cm. 2,8…”
Section: Discussionmentioning
confidence: 98%
“…The goal of OCA is to transplant an allograft with viable chondrocytes and underlying subchondral bone into a recipient socket. 6 Matching a graft to its donor site with respect to size and topography is important to minimizing articular step-off and maintaining near-normal contact pressure. 26 Studies have shown that an elevation of even 0.5 mm to 1 mm over the adjacent articular cartilage at the distal femur can increase contact pressures on the graft up to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…5 Left untreated, these lesions can lead to progressive articular cartilage degeneration, early-onset osteoarthritis, and functional disability. [6][7][8] Understanding cartilage anatomy and morphology is important to evaluating and treating osteochondral and chondral lesions. Longitudinal reference data on cartilage development can aid in interpretation of knee cartilage under pathologic conditions in children and adolescents.…”
mentioning
confidence: 99%
“…Best current evidence does not allow for valid comparison of outcomes associated with treatments for articular cartilage lesions. 60,70,86,161,162 As such, a systematic review by Farr et al concluded that for patients with symptomatic chondral injury, numerous techniques are available to relieve pain and improve function but until data from rigorous clinical trials are available, individual treatment decisions must still be guided by expert extrapolation of available literature using historically sound principles. 70 The authors of the present review article suggest that the peer-reviewed literature in conjunction with sound principles and basic science and preclinical data support the following guidance for clinical application to optimizing outcomes 3,18,28,61,74,117,142,[163][164][165][166][167][168][169][170][171][172] :…”
Section: Basic Science Of Outcomesmentioning
confidence: 99%